Hubungan Pemakaian Alat Pelindung Diri dengan Kejadian Penyakit Kulit pada Pekerja Pengangkut Sampah - Sudarmanto, Sudarmanto; Nurjazuli, Nurjazuli (Jurnal Kesehatan Lingkungan Indonesia, 2002)
Dermatitis is still public health problem. The purpose of this study was to know the relationship between the using of self protected equipment with the occurring of dermatitis on refusal handling worker. Cross sectional design was used in this study. Samples were taken using simple random sampling technique from refusal handling worker in Sleman Regency, Yogyakarta. Total sample were 67 subjects. Dermatitis cases on hand were 26 subjects ( 38,8 % ), whereas the worker who suffer leg’s dermatitis were 31 subjects ( 46,3 % ). The workers didn’t use self protected gloves showed an Odds Ratio of 6,08 higher to suffer dermatitis on hand compared with them who used it. The workers didn’t use self protected boots showed an Odds Ratio of 11,5 higher to suffer leg’s dermatitis compared with them who used it. Key words : Dermatitis, Self Protected Equipment..